A high-resolution electronic rainfall intensity recorder and totaliser - VENUGOPAL , G.; RADHAKRISHNAN, V. (MAUSAM, 1976)
An electronic distant-reading rainfall intensity recorder capable of measuring minute to minute values of the intensity of rain and recoding them on a strip-chart recorder has been designed and constructed at the Instruments Division of the Meteorological Office, Poona. The system measures the intensity of rainfall by converting rain water into drops of equal size and counts the number of drop by an optical-cum-electronic device. The number of counts during every minute interval that constitutes a measure of the intensity of rainfall are recorded on a conventional strip-chart recorder. To measure the total rainfall during any given interval of time, an additional mark is printed on, the chart for every I mm of rainfall. The system that has a resolution of 1/2 mm of rain/hour has been tested during several spells of rainfall at Poona and found to record quite accurately.